Eksistensi Pendistribusian Zakat Secara Online Sebagai Solusi Ekonomi Mustahik di Tengah Pandemi Covid-19 - Lailia, Siti Sa'adatul (Universitas Negeri Surabaya, 2021)
The Covid-19 pandemic does not only affect the big business sector but also affect the small seller such a UMK and UMKM which impact on their decreasing income and even being bankrupt. Thus, the role of tithe is highly needed in order to help reducing those problems. This research is aimed to describe how the tithe distribution conducting via online and became the economic solution for mustahik, the small seller in the Covid-19 pandemic. The research object was the online tithe distribution by IZI in East Java. The method used in this research was descriptive qualitative with interview and documentation as primary and secondary data. The analysis technique was information collection, data reduction, data presentation and data verification. The result shows that online tithe distribution was not able to be conducted optimally since the realization was only 12% compared with offline distribution that reach the number of 88%, thus the online distribution was not able to covers mustahik broader. However, the impact given by the online distribution was not different with the offline distribution.